Association of coagulase-negative staphylococci with orthopedic infections detected by in-house multiplex real-time PCR - Wang, Ying; Liu, Chao; Xia, Wenbo; Cui, Yanxiang; Yu, Linhong; Zhao, Dan; Guan, Xiaoxuan; Wang, Yingdi; Wang, Yani; Li, Yisong; Hu, Jianqiang; Liu, Jie (Frontiers in Microbiology, 2024)
Clinical significance of coagulase-negative staphylococci (CoNS) has been gradually acknowledged in both health care and clinical research, but approaches for their precise discrimination at the species level remain scarce. The current study aimed to evaluate the association of CoNS with orthopedic infections, where accurate and prompt identification of etiology is crucial for appropriate diagnosis and treatment decision making. A 16S rRNA based quantitative PCR (qPCR) assay was developed for the detection of Staphylococcus genus and two panels of 3-plex qPCR assays for further differentiation of six CoNS species with remarkable clinical significance, including S. epidermidis, S. haemolyticus, S. simulans, S. hominis, S. capitis, and S. caprae. All the assays exhibited excellent analytical performance. ΔCq (quantification cycle) between 16S rRNA and CoNS species-specific targets was established to determine the primary CoNS. These methods were applied to detect CoNS in wound samples from orthopedic patients with and without infection. Overall, CoNS were detected in 17.8% (21/118) of patients with clinically suspected infection and in 9.8% (12/123) of patients without any infection symptom (P < 0.05). Moreover, the association with infection was found to be bacterial quantity dependent. S. epidermidis was identified as the predominant species, followed by S. simulans, S. haemolyticus, and S. hominis. Male gender, open injury, trauma, and lower extremity were determined as risk factors for CoNS infections. CoNS positive patients had significantly longer hospitalization duration (20 days (15, 33) versus 13 days (7, 22) for staphylococci negative patients, P = 0.003), which could be a considerable burden for healthcare and individual patients. Considering the complex characteristics and devastating consequences of orthopedic infections, further expanding the detection scope for CoNS may be pursued to better understand the etiology of orthopedic infections and to improve therapeutic strategies.